Problematic questions of block primary measurement attestation of БИНС on dynamic simulator of airplane angular motion - Буриченко, М. Ю.; Кошевая, Л. А. (Proceedings of National Aviation University (archive), 1999)
Described are peculiarities of dynamic attestation of block transducers of angular velocity and accelerometers as multivariable system. Presented is the stand diagram for attestation of block transducers also are proposed regularized spectmm algorithm of structural identification of block transducers and their obstacls